2009
DOI: 10.1161/hypertensionaha.109.135608
|View full text |Cite
|
Sign up to set email alerts
|

Regional Release and Clearance of C-Type Natriuretic Peptides in the Human Circulation and Relation to Cardiac Function

Abstract: Abstract-Production and clearance of plasma C-type natriuretic peptide (CNP) and amino terminal (NT)-proCNP immunoreactivity in the human circulation remain poorly characterized. Accordingly, we have measured arterial and venous concentrations of CNP and NT-proCNP across multiple tissue beds during cardiac catheterization in 120 subjects (age: 64.2Ϯ9.0 years; 73% men) investigated for cardiovascular disorders. The heart, head and neck, and musculoskeletal tissues made the clearest contributions to both plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(71 citation statements)
references
References 42 publications
(49 reference statements)
5
63
0
3
Order By: Relevance
“…It is therefore reasonable to conclude that our findings will have general application -including non pregnant states. It is relevant to note that while plasma CNP values in the current study greatly exceed those likely to be observed in pathophysiological states in humans [20,24,25], they are several orders of magnitude lower than those (1-100 nmol/L) shown to increase BBB permeability in tissue preparations -or achieved after intravenous doses (10 nmol/kg) that increase permeability in mice [12]. Whether equivalent (e.g.…”
Section: Discussionmentioning
confidence: 53%
“…It is therefore reasonable to conclude that our findings will have general application -including non pregnant states. It is relevant to note that while plasma CNP values in the current study greatly exceed those likely to be observed in pathophysiological states in humans [20,24,25], they are several orders of magnitude lower than those (1-100 nmol/L) shown to increase BBB permeability in tissue preparations -or achieved after intravenous doses (10 nmol/kg) that increase permeability in mice [12]. Whether equivalent (e.g.…”
Section: Discussionmentioning
confidence: 53%
“…Because of the low concentrations of CNP in blood from children [16, 17], larger volumes of plasma (> 0.5 mL) are concentrated 4-fold prior to a radioimmunoassay (RIA) to maximize sensitivity. This requirement introduces the potential for loss of the labile peptide during collection and ­processing and limits the use of CNP measurements to specific settings – for example, in detecting an arteriovenous gradient across organs [18, 19] or where the ratio of NTproCNP to CNP has applications in clinical diagnosis. It should be noted that, unlike NTproCNP, interactions of atrial natriuretic peptide (ANP) or B-type natriuretic peptide (BNP) at high plasma concentrations will raise CNP concentrations by competitive displacement of the ligand from the clearance receptor natriuretic peptide receptor C (NPR3) [20-22], which may confound the interpretation of results in some pathological settings.…”
Section: Plasma Cnp Products and Bone Growthmentioning
confidence: 99%
“…Однако процесс её образования изучен недостаточно. CNP очень быстро выводится из организма, концентрация его в плазме чрезвычайно низкая (0,65 пмоль/л) [128]. Он выполняет роль местного регулирующего фактора в тех тканях, где обнаружена его секреция, и дополняет функции ANP и BNP, превосходя их значение в регуляции сосудистого тонуса.…”
Section: активация натрийуретического пептида с-типаunclassified